Camille Flammarion's The Planet Mars: As Translated by Patrick Moore - Flammarion, Camille (Springer, 2016)
Camille Flammarion (1842-1925) began his career at 16 as a human computer under the great mathematician U. J. J. Le Verrier at the Paris Observatory. He soon tired of the drudgery; he was drawn to more romantic vistas, and at 19 wrote a book on an idea that he was to make his own—the habitability of other worlds. There followed a career as France’s greatest popularizer of astronomy, with over 60 titles to his credit. An admirer granted him a chateau at Juvisy-sur-l’Orge, and he set up a first-rate observatory dedicated to the study of the planet Mars. Finally, in 1892, he published his masterpiece, La Planete Mars et ses conditions d’habitabilite, a comprehensive summary of three centuries’ worth of literature on Mars, much of it based on his own personal research into rare memoirs and archives. As a history of that era, it has never been surpassed, and remains one of a handful of indispensable books on the red planet.